EVALUASI KEBIJAKAN PEMERINTAH DALAM PELAKSANAAN PEREMAJAAN (REPLANTING) PERKEBUNAN KELAPA SAWIT DIDUSUN LEMBAH KUAMANG TAHUN 2019 - Ronal Dison; Dewi Wulansari (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2021)
The replanting, which was carried out for the first time in the Kuamang Valley hamlet in 2018, which was funded by the BPDPKS grant, was carried out on an area of ​​110 hectares that participated in the registration of 51 oil palm farmers. However, in its implementation there are various obstacles that make the program not run well in Lembah Kuamang Hamlet. This research method uses a qualitative method with the selection of informants by purposive sampling. The results of the study found that the oil palm replanting policy at KUD Citra Merkadi Dusun Lembah Kuamang had not run according to the rules set out in the Minister of Agriculture Regulation No. 6 of 2018 concerning Palm Oil Relanting Guidelines which occurred due to various obstacles that arise in the implementation of replanting coconut plantations. oil palm in the hamlet of Lembah Kuamang, Pelapat Ilir sub-district, Bungo regency. Constraints in replanting are the difficulty of communicating with operators who handle the implementation of rejuvenation of oil palm plantations in the village of Kuamang valley, the absence of socialization to the community of oil palm farmers and the workforce who have experienced complete cessation due to non-current wages from contractors. As for the efforts made by the Village Unit Cooperative (KUD) in solving the problems that are happening in the valley of Kuamang, the village unit cooperative gives a warning to the contractors and operators and finally decides on a contract with the operator and looks for another contractor who is more professional.